Efectos de la aplicación de tres concentraciones de té de frutas en el cultivo de Fréjol (phaseolus vulgaris l.) sembrado con dos distanciamientos de siembra en el Cantón Bolívar, provincia del Carchi - Nénger Pozo, Marcelo Fabián (2015)
The rehearsal on the effect of the application of three concentrations of Tea of fruits in the fréjol cultivation (Phaseolus vulgaris L.) field with two siembradistancings in the canton Bolívar, county of the Carchi the parish San Vicente of Pusir, geológicamente was executed it corresponds to the subtropical floor with temperature of 29 and 30 °C, altitude among 1900 msnm, relative humidity averages yearly of 75%, annual half precipitation among 500mm. The area of life is dry forest Montano Under (bs - MB). As genetic material the fréjol variety Paragachi was used, coming from the canton Pimampiro, County of Imbabura whose characteristic agronomic they are the following ones: Fréjolarbustivo with small guide, grain of spotted red color with cream, big, elongated ovoid, direct sheath of 14 cm of longitude, their vegetative cycle is of 110 days, the grain has 21% protein. Bush size approximately 45 cm, of abundant foliage of green coloration in tender and of yellow color in mature, the productive cycle for tender is of 2,5 months, for dry fréjol it is of 3,5 months. Yield of 1200 to 2000 kg/ha. The treatments were constituted by three dose of Tea of fruits of 2,5; 5,0 and 7,5 cc/L, with different siembradistancings among 25 cm. between plant and 50 cm between furrow and 30 cm between plant and 60 cm among furrow, in a witness's of traditional siembra presence (20cm. Between plant and 50 cm among furrow). the experimental design of Blocks was used Totally at random with seven treatments and three repetitions using the test of Multiple Ranges from Duncan to 5% of probability............